2019
DOI: 10.1039/c9cc05271b
|View full text |Cite
|
Sign up to set email alerts
|

Why does sulfite reductase employ siroheme?

Abstract: As opposed to heme, siroheme inhibits the charge transfer from the cubane via direct routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
(14 reference statements)
0
12
0
1
Order By: Relevance
“…The prosthetic group assists in the 6-electron reduction of both sulphite and nitrite to allow their incorporation into biological systems at the level of sulphide and ammonia. It has been suggested that siroheme, in preference to heme, allows a more direct charge transfer route to the active center of these enzymes during the catalytic cycle (14). In contrast, heme d1, which like siroheme is not a heme but a dioxo-isobacteriochlorin, is only utilized by one enzyme, a dissimilatory nitrite reductase called cytochrome cd1.…”
Section: Chlsmentioning
confidence: 99%
“…The prosthetic group assists in the 6-electron reduction of both sulphite and nitrite to allow their incorporation into biological systems at the level of sulphide and ammonia. It has been suggested that siroheme, in preference to heme, allows a more direct charge transfer route to the active center of these enzymes during the catalytic cycle (14). In contrast, heme d1, which like siroheme is not a heme but a dioxo-isobacteriochlorin, is only utilized by one enzyme, a dissimilatory nitrite reductase called cytochrome cd1.…”
Section: Chlsmentioning
confidence: 99%
“…The first bears the so-called siroheme, structurally similar to the isobacteriochlorin of F430 cofactor, whose proximal cysteine is bridged to a [4Fe-4S] cluster. The mutual interplay between the two cofactors in SiRs plays a key role in delivering the six electrons needed to convert sulfite to hydrogen sufide [89,90]. The second, also known as Cyt cd1, bears a unique tetrapyrrole ring called heme d1, which shares the same starting scaffold of siroheme [91].…”
Section: Figmentioning
confidence: 99%
“…The roles of the distal lysine and arginine residues (Figure E) include binding and orientation of the substrate and transfer of protons to the catalytic site . In addition to the distal residues there is a Fe 4 S 4 cubane bridged to the cluster which provides electrons to the active site, which may achieve the transformation in three 2e – steps. The same siroheme active site is found in assimilatory nitrite reductases which reduce NO 2 – to NH 4 + . The cytochrome cd 1 nitrite reductase, on the other hand, does not possess the Fe 4 S 4 cluster and uses heme d 1 cofactor and can reduce NO 2 – to NO and not further .…”
Section: Introductionmentioning
confidence: 99%